The Impact of Diorama-Based Instruction on Elementary Students’ Understanding of the Hydrological Cycle in IPAS Learning - Hidayatun Najikha; Khusnul Fajriyah; Wawan Priyanto (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to determine the effectiveness of diorama learning media in improving students' learning outcomes in the hydrological cycle material in the subject of Natural and Social Sciences (IPAS) grade IV SDN Kalicari 02 Semarang. Theoretical framework: This research is based on Edgar Dale's theoretical framework, which states that the use of concrete media provides a richer learning experience and improves students' understanding of abstract concepts. In this context, diorama media is considered to be able to present a three-dimensional visualization of the water cycle process, thus making learning easier to understand and interesting for elementary school students. Literature review:  A literature review shows that concrete media such as dioramas can increase learning effectiveness by stimulating multisensory learning activities and building a more meaningful understanding. In addition, the use of media that is by the characteristics of students can increase motivation, involvement, and absorption of the material. Methods: The research method used is quasi-experimental with a Group Pretest-Posttest Design. The research subjects consisted of 27 students of grade IV A. Data were collected through observation, interviews, and tests. Data analysis was carried out using normality tests and paired sample t-tests. Results: The results showed a significant increase in student learning outcomes, namely the average pretest score of 44.07 increased to 55.22 in the posttest, with a significance value of 0.000 (< 0.05). Implications: The implications of this study show that diorama media can be an effective learning solution for abstract materials, especially at the elementary education level. Novelty: this research lies in the application of diorama media as a concrete tool in science learning that combines science and social concepts, as well as empirically testing its effectiveness in the context of public elementary schools with limited resources.